A prospective study of exercise-associated hyponatremia in two ultradistance triathletes - Speedy, D. B.; Noakes, T. D.; Rogers, I. R.; Hellemans, I.; Kimber, N. E.; Boswell, D. R.; Campbell, R.; Kuttner, J. A. (Clinical Journal of Sport Medicine, 2000)
Es wird das Flüssigkeits- und Natriumgleichgewicht beim Absolvieren eines Ultratriathlons und während der Wiederherstellungsphase in der Nacht bei 2 Triathletinnen untersucht. Die Umgebungstemperatur betrug am Wettkampftag 21°C, die relative Luftfeuchtigkeit 91%, die Wassertemperatur 20,7°C. Beide Probandinnen zeigten während des Wettkampfs eine leichte Hyponatriämie (Na 131 und 130 mmol/L) mit einer Gewichtszunahme von 0,5 und 1,5 kg. Keine hatte einen großen Natriumverlust (24 mmol und 20 mmol). Die Flüssigkeitsaufnahme betrug 733 ml/h und 764 ml/h. Der AVP-Spiegel war nicht erhöht. Beide Triathletinnen zeigten einen Wasserüberschuss während des Wettkampfes (1,5 und 2,5 l) und einen Gewichtsverlust während der Wiederherstellung (2,0 und 4,5 kg).' OBJECTIVE: To study fluid and sodium balance in two ultradistance triathletes. DESIGN: Prospective case study. SETTING: An ultradistance triathlon (3.8 km swim, 180 km cycle, 42.2 km run), and during overnight recovery. Ambient air temperature at 12:00 p.m. race day was 21 degrees C, with a relative humidity of 91%. Water temperature was 20.7 degrees C. SUBJECTS: Two female ultradistance triathletes, ages 30 and 39 years, who were participating in a larger study investigating weight and electrolyte changes in the Ironman triathlon. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Subjects were weighed and had blood drawn for serum sodium concentration, hemoglobin, hematocrit, arginine vasopressin, and aldosterone concentration prior to and after the race, and at 8:00 a.m. the following morning. Sodium and fluid intake and urinary output were measured during recovery. RESULTS: Both subjects developed mild hyponatremia (Na 131 and 130 mmol/L) during the race, with a weight gain (0.5 and 1.5 kg). Neither subject had large sodium losses (24 mmol and 20 mmol). Fluid consumption was 733 ml/h and 764 ml/h. Plasma volume increased during the race (25 and 16%). Arginine vasopressin (AVP) levels were not elevated in either subject (1.2 and 1.9 pmol/L). Both subjects demonstrated a water excess during the race (1.5 and 2.5 L), and lost weight during recovery (2.0 and 4.5 kg). CONCLUSIONS: Hyponatremia resulted from fluid retention in the extracellular space, without evidence of large sodium losses or inappropriate AVP secretion.